CONDITIONED MEDIA OF MESENCHYMAL STEM CELLS RECOVERS PLACENTAL GROWTH FACTOR IN PRISTANE MICE MODEL - MUHAMMAD ADRIANES BACHNAS; AMBAR MUDIGDO; BAMBANG PURWANTO; SRI SULISTYOWATI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: A low level of placental growth factor (PlGF) expression in placenta is strongly correlated with pregnancy loss, prematurity, fetal growth restriction, and preeclampsia. Pristane-induced lupus in mice model has been widely used to present placental damage and poor pregnancy outcomes. Conditioned media (CM), which is medium for culturing mesenchymal stem cells (MSCs), have grown much attention recently. It has rich amount of growth factors, exosomes, microvesicles, and immunomodulatory molecules. These could become beneficial resources to recover poor placentation. Methods: CM taken from the 3rd to 4th passage of the culture were underdone by using explant method of human umbilical cord (hUC). Ninety BALB/c mice were randomly distributed into three groups: Normal, pristane, and pristane + CM group. Mice in normal group were injected with 0.5 ml normal saline and other groups with 0.5 ml pristane. Four weeks later, mice were mated and only pristane + CM group received therapy of CM-MSCs 0.5 ml single dose after pregnancy was confirmed. On day 16, pregnancy was terminated and the placenta was analyzed for PlGF expression using immunoreactive score and statistically tested with analysis of variance. Results: The average of PlGF expression in normal, pristane, and pristane + CM group was 9.528, 3.428, and 10.085, respectively. CM have significantly increase PlGF (p<0.01**) and equal to normal (p=0.301). Conclusion: CM of hUC-MSCs has shown its therapeutical effect among the low level of PlGF in damaged placenta, and potentially would prevent fetal growth restriction and preeclampsia arose from spiral artery remodeling failure.